137Cs estimates of soil erosion rates in a small catchment on a channelized river floodplain in the lower reaches of Yangtze River, China. (November 2019) - Wang, Xiaolei; Xue, Bin; Yao, Shuchun; Yang, Hao; Gu, Zhujun; Yang, Benjun; Zhang, Mingli; Zhu, Ying
Abstract: Channelization significantly affects soil erosion in river floodplains. The object of this study was to use 137 Cs as a tracer to determine the 137 Cs inventory and derived soil erosion rates under various land use types in a catchment on channelized river floodplain in the lower reaches of Yangtze River, China. Sampling was carried out to establish a 137 Cs reference inventory in a 70-year old paddy field located on the shoulder-slope of a local hill. The mean reference inventory of 137 Cs was 1275 Bq m −2, whereas the 137 Cs inventory within the catchment ranged from 284 to 1150 Bq m −2 and the soil erosion rates from −33.3 to −2.4 t ha −1 yr −1, respectively. The dominated land use of paddy in cultivated soils contributed relative low soil erosion. Bamboo and castanea mollissima were preferential for local land uses in uncultivated soils in comparison with woodland and Pinnus massoniana. The rates of soil erosion rates in old tea garden were higher than that in new tea garden. Overall, severe soil erosion and no deposition in the entire catchment occurred in the entire catchment due to the human-induced channelization in the 1970s. Our results suggest that restricting farmland being returned to tea plantations, thereby maintaining the current land use types would reduce soil erosion in river floodplain in the future. Highlights: Quantification of soil erosion on a channelized river floodplain using the 137 Cs technique. Soil erosion was accelerated by man-made channelization of Langchuan River. Returning farmland to tea plantations should be forbidden.